2014
DOI: 10.2337/db13-1502
|View full text |Cite
|
Sign up to set email alerts
|

Abrogating Monoacylglycerol Acyltransferase Activity in Liver Improves Glucose Tolerance and Hepatic Insulin Signaling in Obese Mice

Abstract: Monoacylglycerol acyltransferase (MGAT) enzymes convert monoacylglycerol to diacylglycerol (DAG), a lipid that has been linked to the development of hepatic insulin resistance through activation of protein kinase C (PKC). The expression of genes that encode MGAT enzymes is induced in the livers of insulin-resistant human subjects with nonalcoholic fatty liver disease, but whether MGAT activation is causal of hepatic steatosis or insulin resistance is unknown. We show that the expression of Mogat1, which encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
95
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(114 citation statements)
references
References 45 publications
15
95
4
Order By: Relevance
“…8A), a ratio that is often accepted as a proxy for PKC activation. However, similar to a previous report (39), this change resulted from a reduction in the cytosolic content of PKC⑀, although the membrane PKC⑀ content did not change (Fig. 8B).…”
Section: Overexpression Of Gpat1 and Gpat4 Increased The Protein Ratisupporting
confidence: 90%
See 1 more Smart Citation
“…8A), a ratio that is often accepted as a proxy for PKC activation. However, similar to a previous report (39), this change resulted from a reduction in the cytosolic content of PKC⑀, although the membrane PKC⑀ content did not change (Fig. 8B).…”
Section: Overexpression Of Gpat1 and Gpat4 Increased The Protein Ratisupporting
confidence: 90%
“…The current study shows that the increase in this ratio does not necessarily represent a change in PKC activity; in the present case, the ratio changed because the amount of cytosolic PKC⑀ protein consistently decreased in numerous preparations. A similar discrepancy in the ratio of membrane to cytosolic PKC⑀ and ␦ proteins and PKC activity was reported in mice with deficient hepatic MGAT1 (39). Notably, overexpressing any of five enzymes did not change IRS1 phosphorylation at serine 612 (Figs.…”
Section: Discussionsupporting
confidence: 77%
“…Mice received intraperitoneal injections of ASO directed against Mogat1 or a scrambled control ASO (25 mg/kg body weight; ISIS Pharmaceuticals, Carlsbad, CA) twice a week for 3 weeks. Treatments were initiated after 14 weeks of high fat diet feeding as described (13). Mice were sacrificed after 3 weeks of injections with ASOs, and tissues were harvested, frozen in liquid nitrogen, and stored at Ϫ80°for further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work using antisense oligonucleotides (ASOs) and RNAi approaches have shown that short term hepatic suppression of Mogat1 led to a significant improvement in hepatic insulin signaling and whole-body glucose homeostasis (12,13). The improved glucose tolerance after ASO-mediated knockdown was associated with improved insulin signaling in liver but not other tissues and was not associated with enhanced insulin secretion (13). Although both previous studies demonstrated a profound insulin-sensitizing effect, neither study examined markers of liver injury, inflammation, or fibrosis after knockdown of Mogat1.…”
mentioning
confidence: 99%
“…Since our demonstration of the upregulation of Mogat1 mRNA expression in Agpat2 Ϫ / Ϫ steatotic liver ( 10 ), a few studies using siRNA ( 30 ) or antisense oligonucleotide in an acute setting showed suppression of the expression of Mogat1 in mouse livers ( 31,32 ). This resulted in a modest decrease in the liver TAG and an increase in hepatic insulin signaling and whole body glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%